血清miR-491-5p和miR-21-5p对急性缺血性卒中患者静脉溶栓后出血转化的预测价值 Predictive Value of Serum miR-491-5p and miR-21-5p on Hemorrhagic Transformation after Intravenous Thrombolysis in Acute Ischemic Stroke Patients - 王笑寒1，潘燕1，张小林1，刘坦2 (WANG Xiaohan1, PAN Yan1, ZHANG Xiaolin1, LIU Tan2 ) (Zhongguo cuzhong zazhi)
目的 探讨血清微小RNA（microRNA，miRNA/miR）中miR-491-5p、miR-21-5p对急性缺血性卒中（acute ischemic stroke，AIS）患者静脉溶栓后出血转化的预测价值。 方法 回顾性选取2021年1月—2023年2月南阳市中心医院收治的312例AIS静脉溶栓治疗患者为研究对象，按照静脉溶栓后24 h内出血转化发生情况分为出血转化组（66例）和非出血转化组（246例）。实时荧光定量PCR测定血清miR-491-5p、miR-21-5p表达水平。采用多因素logistic回归分析探讨AIS患者静脉溶栓后出血转化的独立危险因素，以ROC曲线分析血清miR-491-5p、miR-21-5p及二者联合对AIS患者静脉溶栓后出血转化的预测价值。 结果 出血转化组糖尿病、高血压、心房颤动患者比例以及随机血糖水平、NIHSS评分、血清miR-21-5p表达水平高于非出血转化组（P＜0.001），血清miR-491-5p表达水平低于非出血转化组（P＜0.001）。logistic回归分析结果显示，有糖尿病病史（OR 1.907，95%CI 1.088～3.344）、高血压病史（OR 1.928，95%CI 1.105～3.364）、心房颤动病史（OR 2.375，95%CI 1.356～4.159），随机血糖水平升高（OR 1.826，95%CI 1.062～3.138），NIHSS评分升高（OR 3.894，95%CI 1.568～9.671），血清miR-21-5p表达水平升高（OR 4.237，95%CI 1.643～10.925）是AIS患者静脉溶栓后出血转化的独立危险因素（P＜0.001）；而血清miR-491-5p表达水平升高（OR 0.193，95%CI 0.108～0.347）是AIS患者静脉溶栓后出血转化的保护因素（P＜0.001）。ROC曲线显示，血清miR-491-5p、miR-21-5p表达水平预测AIS患者静脉溶栓后出血转化的AUC值分别为0.784（95%CI 0.731～0.838）和0.785（95%CI 0.722～0.847），对应最佳截断值分别为1.21和2.26，二者联合预测的AUC值提升至0.861（95%CI 0.815～0.907）。 结论 血清miR-491-5p表达水平低、miR-21-5p表达水平高是AIS患者静脉溶栓后出血转化的独立危险因素，可作为出血转化的预测指标，联合预测效能良好。 Abstract: Objective To investigate the predictive value of serum microRNA-491-5p (miR-491-5p) and microRNA-21-5p (miR-21-5p) for hemorrhagic transformation after intravenous thrombolysis in patients with acute ischemic stroke (AIS). Methods A total of 312 patients with AIS who underwent intravenous thrombolysis at Nanyang Central Hospital from January 2021 to February 2023 were retrospectively selected as the study objects. They were divided into the hemorrhagic transformation group (66 cases) and the non-hemorrhagic transformation group (246 cases) according to the occurrence of hemorrhagic transformation 24 hours after intravenous thrombolysis. Realtime fluorescence quantitative PCR was used to measure the expression levels of serum miR-491-5p and miR-21-5p. Multivariate logistic regression analysis was used to explore the independent risk factors for hemorrhagic transformation after intravenous thrombolysis in AIS patients. The predictive value of serum miR-491-5p, miR-21-5p, and their combination for hemorrhagic transformation after intravenous thrombolysis in AIS patients was analyzed by ROC curve. Results The proportion of patients with diabetes mellitus, hypertension, and atrial fibrillation in the hemorrhagic transformation group was higher than that in the non-hemorrhagic transformation group (P<0.001). The levels of random blood glucose, NIHSS score, and serum miR-21-5p expression in the hemorrhagic transformation group were also higher than those in the non-hemorrhagic transformation group (P<0.001), while the expression level of serum miR-491-5p was lower than that in the non-hemorrhagic transformation group (P<0.001). Logistic regression analysis showed that a history of diabetes mellitus (OR 1.907, 95%CI 1.088-3.344), a history of hypertension (OR 1.928, 95%CI 1.105-3.364), a history of atrial fibrillation (OR 2.375, 95%CI 1.356-4.159), elevated random blood glucose level (OR 1.826, 95%CI 1.062-3.138), increased NIHSS score (OR 3.894, 95%CI 1.568-9.671), and elevated expression level of serum miR-21-5p (OR 4.237, 95%CI 1.643-10.925) were independent risk factors for hemorrhagic transformation after intravenous thrombolysis in AIS patients (P<0.001). Conversely, elevated expression level of serum miR-491-5p (OR 0.193, 95%CI 0.108-0.347) was the protective factor for hemorrhagic transformation after intravenous thrombolysis in AIS patients (P<0.001). The ROC curve showed that the AUC values of serum miR-491-5p and miR-21-5p expression levels for predicting hemorrhagic transformation after intravenous thrombolysis in AIS patients were 0.784 (95%CI 0.731-0.838) and 0.785 (95%CI 0.722-0.847), respectively. The corresponding optimal cutoff values were 1.21 and 2.26, respectively. The AUC value predicted by the combination of the two increased to 0.861 (95%CI 0.815-0.907). Conclusions Low expression level of serum miR-491-5p and high expression level of miR-21-5p are independent risk factors for hemorrhagic transformation after intravenous thrombolysis in AIS patients. They can be used as risk predictors for hemorrhagic transformation, with good combined predictive efficacy.